Carbazole-substituted dialkoxybenzodithiophene dyes for efficient light harvesting and the effect of alkoxy tail length. (February 2021) - Wagner, Klaudia; Wagner, Pawel; Hasani, Fargol; Barnsley, Jonathan E.; Gordon, Keith C.; Lennert, Annkatrin; Guldi, Dirk M.; Officer, David L.
Abstract: A set of new donor-π-acceptor organic PM dyes, bearing carbazole as electron donor and cyanoacrylic acid as electron acceptor, has been synthesized and fully characterized with particular focus on application in dye-sensitized solar cells (DSSCs). Importantly, a change in 'linker' structure resulted in the electron re-distribution in the oxidized dye, in general, and the localization of the 'electron hole', in particular, when compared with the MK2 benchmark. In addition, modifying the PM dyes with different lengths of alkoxy chains, that is, 1, 4, and 8 carbons, strongly influences the access of the oxidized cobalt ions to the surface affecting recombination, which had an appreciable effect on dye-sensitized solar cell performances. While the performance of the PM dyes was 15–20% lower than MK2, they are considerably easier and less expensive to synthesize, offering excellent potential for future DSSC applications. Graphical abstract: Image 1